Personas sordas y lengua de señas: un enigma en Odontología - Muñoz Quispe, Mirian Elizabeth (2022)
Sign language is the main means of communication for deaf people; consists of the combination of manual, body and facial movements with specific meanings. Among the main barriers faced by this community are the lack of communication, shortage of health services, added to the inexperience and lack of knowledge of sign language by the health professional. This article aims to raise awareness of the importance and need of sign language in dental clinical care and professional training, as well as strategies, tools and recommendations for better care for deaf people. Databases such as SciELO, Google Scholar, PubMed and ScienceDirect were included during the years 2007 and 2021 It was concluded that the main barriers during communication are the little knowledge of sign language in dentists, the little access to interpreters and difficulties in obtaining appointments; affecting the susceptibility to develop oral diseases. The inclusion of sign language courses within the university curriculum provides academic and professional ethics benefits; however, followup is necessary to confirm compliance with the requested parameters. Among the main toolsand strategies, the use of educational videos, the accompaniment of interpreters and, in view of technological development, the use of mobile applications, can facilitate communication. Likewise, a set of recommendations is proposed for the approach of adult and child deaf patients.